Web Database Design to Fulfill Audit Document Requests at PT XYZ: Perancangan Web Database Pemenuhan Pemintaan Dokumen Audit PT XYZ - Ayunda PA. Larasati; Minto Waluyo (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT XYZ is a company that produces fertilizers, non-fertilizers, chemicals and agro-industrial products with various operational activities that support national food security. Continuous supervision and evaluation are needed to ensure that these activities are in accordance with standards and objectives. The Operations and Production Audit Department (AOP) is responsible for conducting supervision through the Annual Supervision Work Program (PKPT) which focuses on monitoring and evaluating the company's operations. However, in its implementation, it is often faced with challenges, such as limited human resources, short audit time, and wide audit coverage that hinders the collection of document requests. Currently, document collection still uses Google Drive and Spreadsheets which are relatively manual and time-consuming. To overcome this problem, a special system is needed to fulfill audit document requests which aims to simplify the process of collecting, monitoring and processing documents. This system is designed using the waterfall method with a MYSQL database and HTML, PHP, CSS, JavaScript programming languages ​​compiled using Visual Studio Code. This system allows for historical storage, so that if it is needed in the future, the auditor does not need to ask the relevant work unit again. The notification feature and organized data access make it easier for auditors to monitor the fulfillment of document requests. Thus, the audit document request system helps the process of collecting, updating, and monitoring documents related to audit document requests to be more organized and efficient, and can reduce human errors and speed up the workflow.